Low Rate of Teriparatide Supplementation for the Treatment of Osteoporotic Pelvic Fractures in Elderly Females - David Novikov MD; Mary Grace Kelley MS; Michael S. Kain MD; Paul Tornetta MD, PhD (Geriatric Orthopaedic Surgery & Rehabilitation)
Background Osteoporotic pelvic fractures in the elderly lead to pain and immobility resulting in decreased quality of life and worsening frailty. Teriparatide has been shown to shorten time to fracture union, diminish pain, and improve mobilization. At our hospital, this medication is prescribed by an outpatient endocrinologist or geriatrician. We hypothesize that elderly female patients sustaining low energy lateral compression (LC) pelvic fractures are not given Teriparatide. This study reports rates of successful Teriparatide initiation and looks for areas of improvement. Materials and Methods A retrospective chart review of stable LC pelvic fractures admitted to a single urban academic level 1 trauma center from January 2012 to February 2021 was conducted. Females over 60 years old with stable LC pelvic fractures were included. Males and those aged less than 60 were excluded. Results 118 females with mean age of 79.1 ± 10.5 were included. Fourteen patients were not eligible for Teriparatide due to medical history, leaving 104 eligible patients. Twenty-eight patients (23.7%) had previous dual energy X-ray absorptiometry (DEXA) scans with mean T-scores of −3.14 ± 1.1 and 61% had Medicare insurance. Orthopaedic services recommended Teriparatide in 100% of cases. Geriatricians or endocrinologists documented evaluations for Teriparatide in 18 (17%), prescribed in 10 (9.6%), and initiated in 7 (6.7%) patients. Insurance type did not significantly differ among those that initiated Teriparatide and those that did not ( p- 0.10). Insurance did not approve the medication in 2 instances and in 1 instance it was discontinued at follow-up. Conclusion Despite level 1 evidence of Teriparatide’s benefit for elderly osteoporotic women with low energy LC pelvic fractures, we failed to initiate treatment in 93% of eligible patients. Barriers to initiation included low rates of medical evaluation for its use and failure of insurance coverage. There are opportunities for multidisciplinary collaboration to increase evaluation for and initiation of Teriparatide. Level of Evidence Cohort Retrospective (level III evidence).